Children and Libraries: Innovative Library services at Marko Lukooya Memorial Community Library during the Covid-19 pandemic, Uganda - Rugambwa, Nina Olivia; Kawalya, Jane; Mutibwa, Lois Nankya (East African Nature and Science Organization, 2025)
Community libraries do not receive financial support from the government, unlike public and academic libraries in Uganda. This study explored the provision of library services during the COVID-19 period by Marko Lukooya Memorial Community Library. The study investigated library services provided by the library, challenges encountered, and strategies that were used to address the challenges faced during the pandemic. A qualitative case study research design was used. Data was collected using face-to-face in-depth interviews and observation methods with library staff and patrons. Standard Operating Procedures were followed during the pandemic by both the participants and researchers to mitigate the risk of the deadly COVID-19 virus. Key findings revealed that the library adapted innovative ways to provide library services to children and the community during the COVID-19 pandemic amidst many challenges. The study recommends training of library staff in information management and more material and financial support by donors, the government, and all well-wishers to support the good work being done by Marko Lukooya Memorial Community Library in Uganda.